Prinsip Good Corporate Governane dalam Pengelolaan Pungutan Sumbangan Pihak Ketiga Pada Perum Perhutani Jateng - Rinitami Njatrijani (Administrative Law and Governance Journal, 2019)
Abstract This study aims to know the Principles of Good Corporate Governance in the Management of Third Party Contribution Donations at the Perum Perhutani Central Java. Research is a study of legal documents described in a qualitative form. The results of the study show that the effort to maintain the implementation of the core business and the Perum Perhutani business plan, in order to mitigate the risk of the relationship between Perhutani and Central Java Province, it is necessary to consider terminating the SP3 levy and turning it into a PNBP as stipulated in Law Number 20 of 1997 concerning Revenue Non-Tax State with all the consequences as regulated Article 4: All Non-Tax State Revenues must be paid immediately as soon as possible to the State Treasury, and Article 5: All Non-Tax State Revenues are managed in the State Budget and Revenue System, then it is necessary to formulate a basis for arranging grants to the Government Central Java Province with the approval of the Minister of Finance. Keywords: Good Corporate Governance, Third Party Charges, Perhutani. Abstark Penelitian ini bertujuan untuk mengatahui Prinsip Good Corporate Governane dalam Pengelolaan Pungutan Sumbangan Pihak Ketiga  Pada Perum Perhutani Jateng. Penelitian merupakan penelitian dokumen hukum yang diuraikan dalam bentuk kualitatif. Hasil penelitian menujukan bahwa upaya menjaga dilaksanakannya core bussines maupun bussines plan Perum Perhutani maka dalam rangka mitigasi risiko hubungan antara perum perhutani dengan Propinsi Jawa Tengah maka perlu dipertimbangkan untuk memberhentkan pungutan SP3 dan merubah menjadi PNBP sebagaimana diatur dalam Undang-Undang Nomer 20 Tahun 1997 tentang Penerimaan Negara Bukan Pajak  dengan segala konsekuensinya sebagaimana diatur Pasal 4 : Seluruh Penerimaan Negara Bukan Pajak wajib disetor langsung secepatnya ke Kas Negara, dan  Pasal 5:  Seluruh Penerimaan Negara Bukan Pajak dikelola dalam sistem Anggaran Pendapatan dan Belanja Negara , selanjutnya perlu  dirumuskan dasar pengaturan hibah  kepada Pemerintah Provinsi Jawa Tengah dengan persetujuan Menteri Keuangan. Kata Kunci: Good Corporate Governance, Pungutan Pihak Ketiga, Perhutani.